The Role of Consumer Ethnocentrism on Perceived Quality, Perceived Price, and Brand Image towards Local Brand Purchase - Mutia, Frida Aryanti (APPS Publications, 2021)
The purpose of this research is to examine the effect of consumer ethnocentrism and its effect on perceived quality, perceived price and brand image toward consumers’ intention to purchase local clothing brand especially young consumer. The research methodology used quantitative method with primary data. The design and development of this questionnaire were based on an initial pretested survey, distributed to 141 college students. The results show that consumer ethnocentrism has a positive effect on consumer perceived quality, perceived price and brand image toward consumers’ intention to purchase local brand in casual clothing category. It also shown that brand image plays a big role in influencing consumers’ purchase intention in buying local clothing brands. This study will give an understanding regarding the influence of government campaign using consumer ethnocentrism towards young consumer’s purchase intention of local brands in Indonesia.